Preparation and in vivo evaluation of red blood cell membrane coated porous silicon nanoparticles implanted with Tb-155 - Ulrika Jakobsson; Ermei Mäkilä; Antti Rahikkala; Surachet Imlimthan; Jarkko Lampuoti; Sanjeev Ranjana; Jouni Heino; Pasi Jalkanen; Ulli Köster; Kenichiro Mizohata; Hélder A. Santos; Jarno Salonen; et al. (ELSEVIER SCIENCE INC, 2025)
Introduction: Porous silicon (PSi) nanoparticles are capable of delivering therapeutic payloads providing targeted delivery and sustained release of the payloads. In this work we describe the development and proof-of-concept in vivo evaluation of thermally hydrocarbonized porous silicon (PSi) nanoparticles that are implanted with radioactive Tb-155 atoms and coated with red blood cell (RBC) membrane (Tb-155-THCPSi). The developed nanocomposites can be utilized as an intravenous delivery platform for theranostic radionuclides.
Methods: THCPSi thin films were implanted with Dy-155 ions that decay to Tb-155 at the ISOLDE radioactive ion-beam (RIB) facility at CERN. The films were processed to nanoparticles by ball-milling and sonication, and subsequently coated with either a solid lipid and RBC membrane or solely with RBC membrane. The nanocomposites were evaluated in vitro for stability and in vivo for circulation half-life and ex vivo for biodistribution in Balb/c mice.
Results: Nanoporous THCPSi films were successfully implanted with Tb-155 and processed to coated nanopartides. The in vitro stability of the particles in plasma and buffer solutions was not significantly different between the particle types, and therefore the RBC membrane coated particles with less laborious processing method were chosen for the biological evaluation. The RBC membrane coating enhanced significantly the blood half-life compared to bare THCPSi particles. In the ex vivo biodistribution study a pronounced accumulation to the spleen was found, with lower uptake in the liver and a minor uptake in the lung, gall bladder and bone marrow.
Conclusions: We have demonstrated, using Tb-155 RIB-implanted PSi nanoparticles coated with mouse RBC membranes, the feasibility of using such a theranostic nanosystem for the delivery of RIB based radionuclides with prolonged circulation time.
Advances in knowledge and implications for patient care: For the first time, the RIB implantation technique has been utilized to produce PSi nanoparticle with a surface modified for better persistence in circulation. When optimized, these particles could be used in targeted radionuclide therapy with a combination of chemotherapeutic payload within the PSi structure.